Applicability of modern information technologies (MIT) to creating and improving Bibliography of University of Wrocław employees and doctoral students database - Zawadzka, Aleksandra (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The transfer of traditional bibliographical record available to date in a codex form as a working document or files available exclusively for library use into a new computer environment and then into the network has changed the bibliography's use and mode of its creation. University of Wrocław employees and doctoral students publications achievements registration database form has now existed for 12 years. It has been a time of dynamic changes as regards technologies and content matter. The present paper describes these elements of the database which mark its innovativeness and strive to meet the requirements of contemporary users.
Keywords: virtual environment; achievement registration; bibliographical database; scholarly communication